Intersectionopoly: A Simulation of the Wage Gap. (April 2017) - Paino, Maria; May, Matthew; Burrington, Lori A.; Becker, Jacob H.
This article describes a simulation activity designed to teach students about the wage gap. The wage gap is an important topic in many sociology classrooms, but it can be difficult to convey the accumulated disadvantage experienced by women and racial/ethnic minorities to students using in-class discussions, lectures, or assigned readings alone. This is particularly true on college campuses that may draw their students from more affluent areas. Classroom simulations, however, provide an opportunity for students with all types of backgrounds to engage their sociological imaginations. In our simulation—Intersectionopoly—we use a modified version of Monopoly based on the wage gap and racial/ethnic minorities' experiences of everyday life to illustrate how members of different racial and gender groups experience disparities in earnings. Unlike other versions of stratified Monopoly, this simulation more closely mirrors the subtle nature of discrimination in the contemporary United States.